2019
DOI: 10.4103/ija.ija_750_18
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcomes in chest trauma patients using chest trauma scoring system: A prospective observational study

Abstract: Background and Aims:Prognostication of chest trauma patients by scoring systems is of vital importance to predict morbidity and mortality. We aimed to predict outcomes in chest trauma patients using chest trauma scoring system (CTS) in Indian patients.Methods:This was a prospective observational study done in a trauma care centre at a tertiary care teaching public hospital. CTS was calculated by scores of age, severity of pulmonary contusion, number of rib fractures and presence of bilateral rib fractures. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Around 31 (38.8%) patients had CTS score ≥ 5 and showed significant association with complications such as pneumonia (p = 0.014), ARDS (p = 0.014), an increased need for ventilation (p = 0.00), and mortality (p = 0.001). Similarly, Harde et al showed that CTS score > 5 is associated with poor outcomes and can be utilized for risk assessment in trauma patients to provide timely management [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 31 (38.8%) patients had CTS score ≥ 5 and showed significant association with complications such as pneumonia (p = 0.014), ARDS (p = 0.014), an increased need for ventilation (p = 0.00), and mortality (p = 0.001). Similarly, Harde et al showed that CTS score > 5 is associated with poor outcomes and can be utilized for risk assessment in trauma patients to provide timely management [10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' information was recorded in a semi-structured questionnaire, which included their sociodemographic characteristics, mode of trauma, primary and associated diagnoses, severity of trauma, and outcomes. Severity of trauma was assessed using the Chest Trauma Scoring (CTS) system, as shown in Figure 1 [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Thoracic trauma accounts for 15-20% of all injuries, with mortality rates varying from 10% to 60%. 3 CTS is derived from several previously identified factors associated with poor outcome. 4 CTS includes 4 parameters including patient age (1-3 points), pulmonary contusions (0-3 points), the number of rib fractures (1-3 points), and bilateral rib fractures (2 points).…”
Section: Introductionmentioning
confidence: 99%
“…This score was first developed using a single institutional sample of 649 patients by Pressley et al and then validated in 1,361 patients at another single institution by Chen et al 4 Chen et al found that this simple score can predict the likelihood of adverse outcomes such as complications and mortality in thoracic trauma patients if CTS is ≥5. 3 Therefore, the authors decided to study the features of CTS in thoracic trauma patients in the Indonesian subpopulation, especially at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic trauma accounts for 15-20% of all injuries, with mortality rates ranging from 10% to 60%. [1][2][3][4] Based on the 2018 Riskesdas, the highest incidence of injuries in Indonesia occurred in the home environment (44.7%), roads (31.4%), and workplaces (9.1%). The percentage of chest trauma incidents is 2.6% in Indonesia and 3.0% in South Sumatra.…”
mentioning
confidence: 99%